The Asosociation between Consumptive Behavior and Depresion Levels among Students Enggaging in Online Loan (Pinjol) Service - Lela Nurlela; Yoga Kertapati; Sukma Ayu Candra Kirana; Selly Indria Cahyani (Universitas STRADA Indonesia, 2026)
Background: High consumptive behavior among students can influence their decision to use online loan services, which are often used to meet consumptive needs. Uncontrolled use of online loans can lead to financial stress and trigger psychological disorders. Purpose: This study aims to determine the relationship between consumptive behavior affecting online loans (pinjol) and the depression levels among students Methods: This study uses an analytical observational design with a cross-sectional approach. The study population consists of 256 students. A simple random sampling technique was used with the Slovin formula, resulting in 156 respondents. The independent variable is consumptive behavior affecting online loans (pinjol), measured using a consumptive behavior instrument, while the dependent variable is depression level, measured using a depression level instrument. Data analysis was performed using the chi-square test. Results: The results show that 140 participants (89.7%) exhibit high consumptive behavior affecting online loans (pinjol), while 86 participants (55.2%) have severe depression. The chi-square test results indicate a significant relationship between consumptive behavior affecting online loans (pinjol) and depression levels among students, with a p-value of (0.000) and ρ-value < 0.05. Conclusion: This study indicates that consumptive behavior affecting online loans (pinjol) is a factor influencing depression levels among students. Therefore, it requires attention from lecturers, educators, and students to address this issue.